2019
DOI: 10.18823/asiatefl.2019.16.1.2.12
|View full text |Cite
|
Sign up to set email alerts
|

The Role of L3 in the Interpretation of Articles with Definite Plurals in L2 English

Abstract: Recent developments in the acquisition of third languages (L3A) have only placed an emphasis on the influence of L1 or L2 on L3A (forward transfer). However, this study investigated the role of L1 or L3 in L2A (backward transfer), by focusing on cross-linguistic variations in generic interpretation on plural NPs. We examined how multilingual (L2 and L3) learners interpret nominals in generic contexts. Two experiments (an acceptability judgement task and a truth value judgement task) are conducted to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In an attempt to explain the comparatively better judgment of the binding domains of reflexives on the part of CEK, we argued that there was reverse transfer from L3 to L2, and the transfer was positive in terms of the interpretation of reflexive bindings. This finding mirrored the pattern in Ahn & Jang (2019). In their study on the interpretation of definite plural NPs, Ahn & Jang found robust evidence of backward transfer from L3 French, L3 Chinese, and L3 Korean on L2 English, and concluded that for multilinguals, L3 transfer trumped any other sources of transfer in their L2 acquisition, which supported Foreign Language Effect Model 1 .…”
Section: Discussionmentioning
confidence: 60%
“…In an attempt to explain the comparatively better judgment of the binding domains of reflexives on the part of CEK, we argued that there was reverse transfer from L3 to L2, and the transfer was positive in terms of the interpretation of reflexive bindings. This finding mirrored the pattern in Ahn & Jang (2019). In their study on the interpretation of definite plural NPs, Ahn & Jang found robust evidence of backward transfer from L3 French, L3 Chinese, and L3 Korean on L2 English, and concluded that for multilinguals, L3 transfer trumped any other sources of transfer in their L2 acquisition, which supported Foreign Language Effect Model 1 .…”
Section: Discussionmentioning
confidence: 60%
“…Medgyes (2001) also points out that learners have different expectations of NNESTs and NESTs. These are the reason why the EFL environment is highly complex and unpredictable (Ahn & Jang, 2019;Alberto, 2013;Domenech & Gomex, 2014;Norliza, 2010;Panisonara & Panisoara, 2012;Ramsdan, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…However, this traditional mirror design is unable to distinguish between models that assume that all PALs can have an effect on L3A, such as the TPM and the hybrid transfer models [ 14 ]. Therefore, through a deformed mirror-image design referencing [ 33 ], we used two experimental groups: the JEC group of L1 Japanese → L2 English → L3 Chinese and the CEJ group of L1 Chinese → L2 English → L3 Japanese, and introduced three control groups: the native Japanese group (nJ group), the native Chinese group (nC group), and the native English group learning L2 Japanese (EJ group). This design can help us confirm the effect of the difference in typological proximity/structural similarity between the languages of PAL and L3 on transfer source selection, provided that all the languages exposed are the same.…”
Section: Methodsmentioning
confidence: 99%